2018
DOI: 10.1103/physreva.98.052310
|View full text |Cite
|
Sign up to set email alerts
|

Staggered quantum walk on hexagonal lattices

Abstract: A discrete-time staggered quantum walk was recently introduced as a generalization that allows to unify other versions, such as the coined and Szegedy's walk. However, it also produces new forms of quantum walks not covered by previous versions. To explore their properties, we study here the staggered walk on a hexagonal lattice. Such a walk is defined using a set of overlapping tessellations that cover the graph edges, and each tessellation is a partition of the node set into cliques. The hexagonal lattice re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Using the same model, it was shown in Ref. 86 that longer and thinner nanotubes exhibit better transport, which we also observed in our model and in the staggered quantum walk on the infinite hexagonal lattice 85 . For graphene based networks we observed a mixed situation regarding the validity of the approximation .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Using the same model, it was shown in Ref. 86 that longer and thinner nanotubes exhibit better transport, which we also observed in our model and in the staggered quantum walk on the infinite hexagonal lattice 85 . For graphene based networks we observed a mixed situation regarding the validity of the approximation .…”
Section: Discussionsupporting
confidence: 87%
“… 27 , 83 , 84 . A discrete-time staggered quantum walk model was used to compute the mean-square displacement on hexagonal lattices and to solve the spatial search problem 85 . The article 86 focuses on excitation source-to-sink transport for percolated coined quantum walks on nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…In a context close to the spatial search algorithm, Childs et al [9] showed that the propagation of a particle between a particular pair of nodes is exponentially faster when driven by a continuous-time quantum walk compared to a random walk. There are many papers in the literature addressing this formulation in both the discrete-time [8,10,11,12] and continuous-time [3,13,14,15,16,17,18,19,20,21] cases. Experimental implementations of search algorithms by continuous-time quantum walk are described in [22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The relation of the SQW with other quantum walk models was studied in [19,20,8,14,23]. It has been also applied in the development of quantum algorithms [18,5,21], and in physical implementations [12].…”
Section: Introductionmentioning
confidence: 99%